Both introns and long 3'-UTRs operate as cis-acting elements to trigger nonsense-mediated decay in plants - Kertész, Sándor; Kerényi, Zoltán; Mérai, Zsuzsanna; Bartos, Imre; Pálfy, Tamás; Barta, Endre; Silhavy, Dániel (Nucleic acids research, 2006)
Nonsense-mediated mRNA decay (NMD) is a eukaryotic quality control mechanism that identifies and eliminates aberrant mRNAs containing a premature termination codon (PTC). Although, key trans-acting NMD factors, UPF1, UPF2 and UPF3 are conserved in yeast and mammals, the cis-acting NMD elements are different. In yeast, short specific sequences or long 3'-untranslated regions (3'-UTRs) render an mRNA subject to NMD, while in mammals' 3'-UTR located introns trigger NMD. Plants also possess an NMD system, although little is known about how it functions. We have elaborated an agroinfiltration-based transient NMD assay system and defined the cis-acting elements that mediate plant NMD. We show that unusually long 3'-UTRs or the presence of introns in the 3'-UTR can subject mRNAs to NMD. These data suggest that both long 3'-UTR-based and intron-based PTC definition operated in the common ancestors of extant eukaryotes (stem eukaryotes) and support the theory that intron-based NMD facilitated the spreading of introns in stem eukaryotes. We have also identified plant UPF1 and showed that tethering of UPF1 to either the 5'- or 3'-UTR of an mRNA results in reduced transcript accumulation. Thus, plant UPF1 might bind to mRNA in a late, irreversible phase of NMD.